Wrist, but Not Back, Isometric Contraction Induced Widespread Hypoalgesia in Healthy Participants - Mailloux, Catherine; Wideman, Timothy H.; Massé-Alarie, Hugo (Frontiers in Pain Research, 2021)
Objective: Exercise may reduce pain sensitivity. This phenomenon called exercise-induced hypoalgesia is observed in different types of exercises and involves the activation of endogenous pain modulation systems. Although the effect of limb exercise on pain sensitivity has often been tested, few studies explored the impact of back exercises that are often used to treat low back pain. The main objective is to measure the effect of back-muscle exercise on pain sensitivity and compare it to the effect of a limb-muscle exercise. Methods: Twenty-three participants who were pain-free performed a 4-min wrist flexion isometric contraction followed by a 4-min low back extension, separated by a 20-min break. Pressure pain thresholds were tested at two low back (S1 spinous process, lumbar erector spinae muscle) and two wrist (capitate bone, wrist flexor muscles) sites before and after each exercise. For each exercise, sites were considered as remote or local in relation to the muscles contracted during the exercise. An independent sample of 11 participants was recruited to confirm the influence of low back extension on pain sensitivity. Results: Wrist exercise induced a larger increase in pain sensitivity than back exercise at the remote site. Only wrist exercise induced a hypoalgesia effect at both the local and the remote sites. Back exercise induced a similar effect in the independent sample. Conclusions: This study showed that back and wrist exercises induced a distinct effect on pain sensitivity in participants who were pain-free. The wrist exercise induced a systemic reduction in pain sensitivity (locally and remotely), whereas the back exercise did not. This differential effect may be present because wrist exercise induced most fatigue compared with the back exercise.